A β-Ketoacyl-CoA Synthase Is Involved in Rice Leaf Cuticular Wax Synthesis and Requires a CER2-LIKE Protein as a Cofactor. Issue 2 (2nd December 2016) - Wang, Xiaochen; Guan, Yuanyuan; Zhang, Du; Dong, Xiangbai; Tian, Lihong; Qu, Le Qing
Abstract : WSL4 physically interacts with CER2-like protein, catalyzing the elongation of very-long-chain fatty acids longer than 24 carbons, and is involved in the synthesis of cuticular wax in rice leaf. Abstract: Cuticular waxes are complex mixtures of very-long-chain fatty acids (VLCFAs) and their derivatives, forming a natural barrier on aerial surfaces of terrestrial plants against biotic and abiotic stresses. In VLCFA biosynthesis, β-ketoacyl-CoA synthase (KCS ) is the key enzyme, catalyzing the first reaction in fatty acid elongation and determining substrate specificity. We isolated a rice ( Oryza sativa ) wax crystal-sparse leaf 4 ( WSL4 ) gene using a map-based cloning strategy. WSL4 is predicted to encode a KCS, a homolog of Arabidopsis ( Arabidopsis thaliana ) CER6. Complementation of the mutant wsl4-1 with WSL4 genomic DNA rescued the cuticular wax-deficient phenotype, confirming the function of WSL4 . The load of wax components longer than 30 carbons (C30) and C28 were reduced markedly in wsl4-1 and wsl4-2 mutants, respectively. Overexpression of WSL4 increased the cuticular wax load in rice leaves. We further isolated a cofactor of WSL4, OsCER2, a homolog of Arabidopsis CER2, by coimmunoprecipitation and confirmed their physical interaction by split-ubiquitin yeast two-hybrid experiments. Expression of WSL4 alone in elo3 yeast cells resulted in increased C24 but did not produce VLCFAs of greater length, whereas expressing OsCER2 alone showed no effect. Coexpression of WSL4 and OsCER2 in elo3 yeast cells yielded fatty acids up to C30. OsCER2 with a mutated HxxxD motif (H172E, D176A, and D176H) interrupted its interaction with WSL4 and failed to elongate VLCFAs past C24 when expressed with WSL4 in elo3 yeast cells. These results demonstrated that WSL4 was involved in VLCFA elongation beyond C22 and that elongation beyond C24 required the participation of OsCER2.